2019
DOI: 10.1101/686121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CNN explains tuning properties of anterior, but not middle, face-processing areas in macaque IT

Abstract: Recent computational studies have emphasized layer-wise quantitative similarity between convolutional neural networks (CNNs) and the primate visual ventral stream. However, whether such similarity holds for the face-selective areas, a subsystem of the higher visual cortex, is not clear. Here, we extensively investigate whether CNNs exhibit tuning properties as previously observed in different macaque face areas. While simulating four past experiments on a variety of CNN models, we sought for the model layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…4 At the same time, a number of groups have found that activity in deep layers of convolutional neural networks can explain significant variance of neural responses in ventral temporal cortex. 26,[29][30][31][32] Here, we extend these earlier results by comparing the efficacy of a large number of different computational models of face representation to account for neural activity in face patch AM. We were especially interested in how the 2D morphable model, a simple and explicit graphical model, would compare to VGG-face, a black box deep neural network dedicated to face recognition containing hundreds of thousands of parameters and trained on nearly a million (982,803) facial images.…”
Section: Discussionsupporting
confidence: 59%
“…4 At the same time, a number of groups have found that activity in deep layers of convolutional neural networks can explain significant variance of neural responses in ventral temporal cortex. 26,[29][30][31][32] Here, we extend these earlier results by comparing the efficacy of a large number of different computational models of face representation to account for neural activity in face patch AM. We were especially interested in how the 2D morphable model, a simple and explicit graphical model, would compare to VGG-face, a black box deep neural network dedicated to face recognition containing hundreds of thousands of parameters and trained on nearly a million (982,803) facial images.…”
Section: Discussionsupporting
confidence: 59%